Results From a Survey of American Geriatrics Society Members' Views on Physician‐Assisted Suicide. Issue 1 (2nd December 2019) - Rosenberg, Lisa J.; Butler, Jorie M.; Caprio, Anthony J.; Rhodes, Ramona L.; Braun, Ursula K.; Vitale, Caroline A.; Telonidis, Jacqueline; Periyakoil, Vyjeyanthi S.; Farrell, Timothy W.
Abstract : BACKGROUND: Physician‐assisted suicide (PAS) is a controversial practice, currently legal in nine states and the District of Columbia. No prior study explores the views of the American Geriatrics Society (AGS) membership on PAS. DESIGN: We surveyed 1488 randomly selected AGS members via email. PARTICIPANTS: A total of 369 AGS members completed the survey (24.8% response rate). ANALYSIS: We conducted bivariate correlation analyses of beliefs related to support for PAS. We also conducted qualitative analysis of open‐ended responses. RESULTS: There was no consensus regarding the acceptability of PAS, with 47% supporting and 52% opposing this practice. PAS being legal in the respondent's state, belief that respect for autonomy alone is sufficient to justify PAS, and intent to prescribe or support requests for PAS if legal in state of practice all correlated with support for PAS. There was no consensus on whether the AGS should oppose, support, or adopt a neutral stance on PAS. Most respondents believed that PAS is more complex among patients with low health literacy, low English proficiency, disability, dependency, or frailty. Most respondents supported mandatory palliative care consultation and independent assessments from two physicians. Themes identified from qualitative analysis include role of the medical profession, uncertainty of the role of professional organizations, potential unintended consequences, autonomy, and ethical and moral considerations. CONCLUSION: There was no consensus among respondents regarding the acceptability of PAS. Respondents expressed concern about vulnerable older populations and the need for safeguards when responding to requests for PAS. Ethical, legal, and policy discussions regarding PAS should consider vulnerable populations. J Am Geriatr Soc 68:23–30, 2019